Proposed Marketing Strategy To Enhance Brand Awareness Of Perfume Industry In Indonesia (Case Study : Charma Scents) - Chyntia Paramitha Azka; Novika Candra Astuti (Journal of Research in Social Science and Humanities, 2026)
CharmaScents, a small and medium enterprise established in 2023, faces a critical business challenge of persistently low sales performance despite operating within Indonesia's rapidly growing perfume market, projected to reach USD 427.81 million with a CAGR of 3.35% through 2030. Through systematic root cause analysis, this research identifies that the fundamental business issue is not product quality, pricing strategy, or distribution channels, but rather critically low brand awareness among target consumers, with 58.6% of surveyed respondents having never heard of the brand. This creates a significant gap between market potential and actual sales performance, as brand awareness serves as the essential first step in consumer decision-making processes, particularly for experiential products like fragrances where sensory perception and emotional value play crucial roles. The research addresses a significant gap in understanding how emerging local perfume SMEs in developing markets can strategically build brand awareness through digital marketing within resource-constrained environments, particularly when marketing sensory products that traditionally require physical testing but are increasingly purchased online without prior experience. This study is especially relevant given that 73% of Generation Z consumers in Indonesia now engage in blind-buying behavior for perfumes based on digital content and social proof, representing a fundamental shift in consumer behavior that existing literature has not adequately explored within the context of local brand development strategies. This research employs a comprehensive mixed-methods approach integrating quantitative consumer surveys and qualitative stakeholder interviews to develop evidence-based marketing strategies. The quantitative component utilized a structured questionnaire distributed to 249 respondents from Generation Z and Millennial demographics in the Jabodetabek area, with data analyzed through IBM SPSS Statistics using validity testing, reliability testing, descriptive statistical analysis, and cluster analysis. The qualitative component consisted of semi-structured interviews with CharmaScents' co-founder, providing critical insights into internal capabilities and strategic positioning. The theoretical foundation integrates Kotler and Armstrong's Marketing Strategy and Marketing Mix theory, Barney's Resource-Based View, Porter's Value Chain and Five Forces, and PESTLE framework, synthesized through SWOT and TOWS analysis, ultimately applying Ansoff's Matrix to identify the most appropriate growth strategy. The research findings confirm critically low brand awareness as the primary barrier to sales growth, with cluster analysis identifying Value Seekers (57% of respondents) as the optimal target segment, young middle-income professionals aged 25-35 with stronger purchasing capacity, systematic decision-making processes, and high engagement with digital platforms. Internal analysis reveals that while CharmaScents possesses valuable resources including high-quality products, unique archetype-based storytelling, and authentic Indonesian cultural narrative, these strengths remain underutilized due to inconsistent digital content execution, limited marketing budget, and insufficient social proof. External analysis highlights favorable conditions including government support for local brands, growing consumer preference for domestic products, and e-commerce adoption, though tempered by intense competitive rivalry, low entry barriers, and minimal switching costs in the marketplace. Based on these findings, the research proposes a Market Penetration strategy comprising three integrated components. First, CharmaScents should develop a systematic digital content marketing framework centered on consistent storytelling campaigns aligned with personality archetypes, leveraging Instagram, TikTok, Shopee, and Tokopedia through structured content calendars, user-generated content, and strategic micro-influencer collaborations. Second, the company should introduce value-based product offerings including trial kits and scent bundles designed to reduce purchase barriers and encourage product exploration in online environments. Third, CharmaScents should selectively participate in offline activation events in urban areas to enable sensory product experience while reinforcing digital narratives. The implementation follows a phased approach prioritizing immediate actions (0-3 months) focused on establishing consistent content systems and launching trial offerings, medium-term initiatives (3-6 months) emphasizing micro-influencer partnerships and marketplace optimization, and long-term strategies (6-12 months) involving selective offline activations and community-building programs. This resource-conscious approach aims to increase brand awareness among Value Seeker consumers, build trust through social proof, and convert market potential into sustained sales growth while remaining aligned with CharmaScents' limited organizational capacity and affordable luxury positioning.